“DURMA” (Model Penciptaan Pesan dan Kesan Musik Melalui Pembenturan Teks Lirik dengan Ekpresi Musik) - Manggala, Bondan Aji (Acintya, 2020)
ABSTRACT This article is part of a report on the results of artistic research (works of music) in the field of music. Briefly expresses experience and some knowledge findings related to the process of creating musical works of art. "Durma" is an editorial for this artwork, which contains three works of music with a popular music creation approach. Inspired by the anxiety of observing the infertility of creativity in the area of popular music in Indonesia, through "Durma" the thought was made to model the creativity of popular music by paying attention to the clash of lyric texts with musical expressions to produce messages and impressions of songs that are not public. In the habits of popular music, the elements of lyric text and musical expression are linear and mutually reinforcing relationships. It has never been imagined before that when a popular musical creation thinks a little freely and tries to clash ideas with an established knowledge of popular music creation, it will instead create ambiguity and the complexity of a refreshing taste. The outputs of the "Durma" artistic research include (1) art work products in the form of audio recordings of three songs entitled (a) Candles, (b) Girls, and (c) Good Night, (2) research reports, and (3) scientific publications articles that unravel the knowledge behind this work process.Keywords : Music creation, popular, clash of musical expressions and lyric texts ABSTRAK Artikel ini adalah bagian dari laporan hasil penelitian artistik (karya musik) di bidang musik. Secara singkat, ini mengungkapkan pengalaman dan beberapa temuan pengetahuan terkait dengan proses penciptaan karya seni musik. "Durma" adalah editorial untuk karya seni ini, yang berisi tiga karya musik dengan pendekatan penciptaan musik populer. Terinspirasi oleh kecemasan mengamati ketidaksuburan kreativitas di bidang musik populer di Indonesia, melalui "Durma" pemikiran dibuat untuk memodelkan kreativitas musik populer dengan memperhatikan benturan teks lirik dengan ekspresi musik untuk menghasilkan pesan dan tayangan lagu yang tidak umum. Dalam kebiasaan musik populer, unsur-unsur teks lirik dan ekspresi musik adalah hubungan linier dan saling menguatkan. Belum pernah terbayangkan sebelumnya bahwa ketika sebuah ciptaan musik populer berpikir sedikit dengan bebas dan mencoba untuk bertabrakan dengan pengetahuan mapan tentang ciptaan musik populer, ia malah akan menciptakan ambiguitas dan kompleksitas rasa yang menyegarkan. Output dari penelitian artistik "Durma" meliputi (1) produk karya seni dalam bentuk rekaman audio dari tiga lagu berjudul (a) Lilin, (b) Gadis, dan (c) Selamat Malam, (2) laporan penelitian, dan (3) artikel publikasi ilmiah yang mengungkap pengetahuan di balik proses kerja ini. Kata kunci: Penciptaan musik, populer, benturan ekspresi musik dan teks lirik